Technological competencies in cardiovascular nursing education - Rika Miyahara Kobayashi; Maria Madalena Januário Leite (SciELO, 2015)
Abstract OBJECTIVE To identify the perception of the coordinators of the Specialization Courses in Cardiovascular Nursing about inserting content from Information and Communication Technology (ICT) and analyze them in relation to the technological competencies and regarding its applicability, relevance and importance in assisting, teaching and management. METHOD Descriptive study with 10 coordinators of the Specialization course in Cardiologic Nursing, who replied to the questionnaire for the development of technological competency adapted from the Technology Initiative Guidelines Education Reforms (TIGER), and analyzed using the Delphi technique for obtaining consensus and scored according to the relevance, pertinence and applicability using Likert scale according to degree of agreement. RESULTS Six courses developed ICT content. The contents of the TIGER were considered relevant, pertinent and applicable. CONCLUSION The coordinators recognize the need for technological competencies of the Cardiovascular Nurse for healthcare applicability.